Microbial fuel cells and osmotic membrane bioreactors have mutual benefits for wastewater treatment and energy production. (1st July 2016) - Hou, Dianxun; Lu, Lu; Ren, Zhiyong Jason
Abstract: This study demonstrates that microbial fuel cells (MFCs) and osmotic membrane bioreactors (OMBRs) can be mutually beneficial when integrated together for wastewater treatment. When connecting MFCs with OMBRs, the solute buildup increased conductivity and buffer capacity, which greatly increased MFC power density from 3 W/m 3 up to 11.5 W/m 3 . In turn, the MFCs conditioned and reduced sludge production and therefore reduced forward osmosis (FO) membrane fouling. The MFC-OMBR equipped with new thin-film composite (TFC) membrane showed excellent organic (>95%) and phosphorus removal (>99%) and therefore maintained effluent sCOD below 20 mg/L. However, the nitrogen removal was limited due to the negative surface charge of the thin-film composite membrane and solution chemistry, which led to higher flux of ammonium toward the OMBR draw solution. Further studies are needed to improve nitrogen removal, reduce fouling, and optimize system integration. Graphical abstract: Highlights: A two-stage MFC-OMBR system was developed and the mutual benefits were revealed. The OMBR solute accumulation promoted higher MFC power production. The MFCs conditioned and reduced sludge load for OMBR and reduced membrane fouling. The new TFC membrane showed excellent organic and phosphorus removal.